Dolphins’ Willingness to Participate (WtP) in Positive Reinforcement Training as a Potential Welfare Indicator, Where WtP Predicts Early Changes in Health Status - Clegg, Isabella L. K.; Rödel, Heiko G.; Mercera, Birgitta; van der Heul, Sander; Schrijvers, Thomas; de Laender, Piet; Gojceta, Robert; Zimmitti, Martina; Verhoeven, Esther; Burger, Jasmijn; Bunskoek, Paulien E.; Delfour, Fabienne (Frontiers in Psychology, 2019)
Welfare science has built its foundations on veterinary medicine and thus measures of health. Since bottlenose dolphins (Tursiops truncatus) tend to mask symptoms of poor health, management in captivity would benefit from advanced understanding on the links between health and behavioural parameters, and few studies exist on the topic. In this study, four representative behavioural and health measures were chosen: health status (as qualified by veterinarians), percentage of daily food eaten, occurrences of new rake marks (proxy measure of social activity), and willingness to participate (WtP) in Positive Reinforcement Training sessions as qualitatively measured by their caretakers. These data were collected multiple times a day, every day over the course of a year from a multi-facility, large sample size (ndolphins= 51), allowing powerful analyses of the relationships between measures. First, it was found that dolphins with a higher WtP score also had a significantly better health status, ate a higher percentage of their daily food, and a lower occurrence of new rake marks. In addition, the WtP score was significantly lower up to 3 days before the weekly veterinary diagnosis of a decrease in health state; the percentage of daily food eaten and new rake mark measures did not show any significant change before such a diagnosis. These results suggest that WtP in training sessions is a potential behavioural measure of dolphin welfare, and an indicator of early changes in the dolphins’ health state. We therefore suggest measurement of WtP as a more practical and non-invasive tool to support veterinary care and general management. More work needs to be conducted to elucidate the influence of social behaviour on health, and to identify other potential welfare indicators, but this long-term study has shown that qualitative measures can be both practical and valid when assessing dolphin welfare.